1999
DOI: 10.2307/166194
|View full text |Cite
|
Sign up to set email alerts
|

Popular Religions and the Building of Democracy in Latin America: Saving the Tocquevillian Parallel

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Center for Latin American Studies at the University of Miami is collaborating with JSTOR to digitize, preserve and extend access to Journal of Interamerican Studies and World … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…Many members of both Sagrada Familia Lutheran Church and the Misión Católica de Nuestra Señora de las Américas did indeed, through processes of religious conversion, become confident, articulate, and capable persons with the habits and dispositions necessary for thriving, participatory, democratic societies, but they lacked opportunities to exercise citizenship in the United States because of their status as undocumented immigrants. Technically, they constituted perhaps the most extreme case of "mere inhabitants" (Ireland, 1999) of the society in which they resided.…”
Section: A Cautionary Conclusionmentioning
confidence: 99%
“…Many members of both Sagrada Familia Lutheran Church and the Misión Católica de Nuestra Señora de las Américas did indeed, through processes of religious conversion, become confident, articulate, and capable persons with the habits and dispositions necessary for thriving, participatory, democratic societies, but they lacked opportunities to exercise citizenship in the United States because of their status as undocumented immigrants. Technically, they constituted perhaps the most extreme case of "mere inhabitants" (Ireland, 1999) of the society in which they resided.…”
Section: A Cautionary Conclusionmentioning
confidence: 99%
“… Hallum has pointed out that comparisons of this kind can shed light on the ‘pragmatic reasons women in Latin America are turning to Pentecostalism’ (Hallum : 170). Scholars who wrote about the relevance and usefulness of this kind of comparison include Burdick (, ), Ireland (), Mariz (), and Smith (). …”
mentioning
confidence: 99%
“…A number of scholars, inspired by de Tocqueville (1835), have put forth the idea that civil society is essentially associational life, as well as patterns of association that foster habits of civility and organization in the actions of citizens in a democratic polity (Brysk 2001;Putnam 2000;1993;Galston 2000;Ireland 1999;Booth & Richard 1998;Foley & Edwards 1996;de Tocqueville 1984de Tocqueville , 1835. This form of civil society is known as civil society I.…”
Section: Civil Societymentioning
confidence: 99%
“…Progressive Catholicism created an ethic of public engagement because doctrinally God is served through other humans. This public engagement is enhanced through the Progressive Church's mission to serve the underprivileged and the belief that a just and peaceful world can be achieved through the cooperative interaction of humans (Ireland 1999, Levine 1992, Drogus 1992. Studies of CEBs have shown how adherents have engaged in collective struggles for land, services, and rights and liberties (for a review see Ireland 1999).…”
Section: Points Out Presidentmentioning
confidence: 99%
See 1 more Smart Citation